Nilai-Nilai Syariah dan Kualitas Pelayanan sebagai Determinan Kepuasan Mahasiswa pada Ritel Kampus - Naila Himmatul Chusna; Nur Kholidah; Miqdam Maufur (Indonesian Journal of Management & Islamic Business, 2026)
This study aims to evaluate the empirical determinants of student satisfaction at Maslahat Mart, a campus retail cooperative operating within the Islamic College of Syubbanul Wathon. In this structural model, the research incorporates service quality (X1) and Sharia values (X2) as the core independent variables. Adopting an inferential quantitative approach, the study utilizes multiple linear regression analysis via SPSS software. The research population comprises all 693 registered active student members of the Islamic College of Syubbanul Wathon. A sample size of 254 respondents was calculated using the Slovin formula, distributed proportionately across each academic study program through a probability sampling technique. Primary data collection was executed via a closed-ended questionnaire utilizing a five-point Likert scale. The empirical results demonstrate that the service quality variable exerts a positive but statistically insignificant effect on student satisfaction. Conversely, the implementation of Sharia values exhibits a positive and highly significant effect on student satisfaction. Simultaneously, both independent variables exert a significant collective influence on the dependent variable. The coefficient of determination (R2) value of 0.491 indicates that service quality and Sharia values are collectively capable of explaining 49.1% of the total variance in student satisfaction, while the remaining 50.9% is driven by external factors outside the scope of this investigation. These findings confirm that micro-consumer satisfaction in a faith-based educational environment depends heavily on the operationalization of Sharia values as systemic business ethics, rather than mere conventional service performance.